Antimicrobial and Antioxidant Activity of Endophyte Bacteria Associated with Curcuma longa Rhizome - Sulistiyani, Sulistiyani; Ardyati, Tri; Winarsih, Sri (Graduate School, Universitas Brawijaya, 2016)
Most cases of bacterial resistance towards antibiotics, encourage various efforts to gain new sources of antibiotics. Endophyte bacteria is a microorganism has important role as the producer of bioactive compounds. Endophyte bacteria from Curcuma longa with antimicrobial and antioxidant activities have not been studied yet. Curcuma longa has been utilized as the main ingredients of traditional herbal medicines (jamu). The objective of this research was to investigate the antimicrobial and antioxidant activity of endophyte bacteria associated with Curcuma longa rhizome. Based on morphological characteristics of bacterial colonies, eight endophyte bacteria was isolated from Curcuma longa rhizome. Screening of endophyte isolate has antimicrobial activity was done using agar well diffusion method. The culture supernatant of each endophyte isolate was dropped on agar well against pathogenic bacteria Salmonella enterica ser. Typhi, Staphylococcus aureus and yeast Candida albicans. Three endophyte isolates K3, K2 and M1b showed antimicrobial activity against pathogenic bacteria and yeast. Isolate K3 showed strong antimicrobial activity against C. albicans and S. aureus, however, isolate K2 and isolate M1b showed antimicrobial activity against Salmonella enterica ser. Typhi and S. aureus, respectively. Those endophyte bacteria also had antioxidant activity shown by scavenging ability toward DPPH radical with consecutive percentage of isolate K3 (72.3 %), K2 (51.3 %) and M1b (64.6 %). Isolate K3 showed the highest antimicrobial and antioxidant activity. Based on biochemical characteristics using Microbact 24E kit, isolate K3 was identified as Paenibacilus alvei and isolate K2 as Enterobacter agglomerans. Keywords: antimicrobial, antioxidant, Curcuma longa's rhizome, endophyte bacteria.